Harnessing Artificial Intelligence in Higher Education Research: Prospects and Challenges - Afusat Titilayo Alabi; Adeseko Sunday Olaifa; Ebunlomo Oreoluwa Olaifa; Yinusa Ayinla Yusuf (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
The rapid growth of artificial intelligence (AI) has begun to reshape higher education worldwide, opening new opportunities for innovation in teaching, learning, and research. In Nigeria, where higher education research often struggles with limited funding, infrastructural deficits, and restricted access to global resources, the integration of AI offers both promise and uncertainty. This paper critically examines the prospects and challenges of harnessing AI in higher education research in Nigeria, with a view to identifying strategies that can support its responsible adoption. Adopting a position paper methodology, the study relies on a review and synthesis of secondary sources, including scholarly articles, policy documents, and institutional reports. The analysis was guided by thematic categorisation of opportunities and challenges, with emphasis on the Nigerian higher education context. The findings indicate that AI can enhance efficiency in research processes, broaden access to global scholarship, promote personalised and inclusive studies, and safeguard research quality. However, infrastructural weaknesses, limited technical skills, concerns over data privacy, algorithmic bias, and the absence of strong regulatory frameworks remain significant barriers to adoption. The paper concludes that the responsible integration of AI requires strategic investments in digital infrastructure, researcher capacity-building, ethical safeguards, and locally relevant AI tools. By addressing these issues, Nigerian universities can leverage AI to advance innovation, inclusivity, and sustainability in higher education research, contributing more effectively to national and global knowledge economies.